THE DEVELOPMENT OF RITMIC GYMNASTIC MODEL TO IMPROVE BASIC MOVEMENT AND INTEREST IN RYTMIC GYMNASTIC - Jeane Betty Kurnia Jusuf; Andri Tria Raharja; Nanda Alfian Mahardhika (Acitya: Journal of Teaching and Education, 2019)
Physical education learning in elementary schools aimed to improve the students’ growth, skills and agility, increase knowledge and intelligence, and instill positive attitudes in students. This research aimed at producing models of good rhythmic gymnastics and effective for improving basic movements and interest in rhythmic gymnastics. This research applied research and development method (RnD). The steps were: (1) a preliminary study, (2) planning, (3) the design of earlier drafts, (4) validation earlier drafts and revisions, (5) testing small scale, (6) and large-scale testing, and (7) the final product, and (8) the effectiveness of the test. Small-scale and large-scale trials were applied in different school. Instruments were: (1) interview, (2) experts questionnaires, (3) questionnaire for teachers and students, and (4) a rubric effectiveness test assessment. The data was analyzed by using qualitative descriptive. The results were rhythmic gymnastics models for elementary school upscale students packaged in form of a DVD and a guidebook were considered good and effective, therefore the learning model developed fit for usage.